Levels of unmet needs and distress amongst adolescents and young adults (AYAs) impacted by familial cancer. Issue 9 (25th April 2017) - Patterson, P.; McDonald, F.E.J.; White, K.J.; Walczak, A.; Butow, P.N.
Abstract: Objective: To describe levels of, and relationships between, distress and psychosocial unmet needs in adolescents and young adults (AYAs) with a family member with cancer. Methods: Adolescents and young adults (12‐24 years old) with a living sibling or parent with cancer participated. Participants completed demographics, the Kessler 10 (K10) distress scale and the Sibling or Offspring Cancer Needs Instruments. Descriptive statistics were obtained for all measures, item‐level frequencies were examined to identify common unmet needs, and relationships between distress and unmet needs were explored. Results: Average sibling (N = 106) and offspring (N = 256) distress levels were in the high range (K10total = 22‐30), with 29.6% and 31.6% in the very high range (K10total = 31‐50), respectively. Siblings had mean = 19.7 unmet needs (range 0‐45), 66% had ≥10 unmet needs, and 44% of the 45 needs were unmet on average. Offspring had mean = 22.4 unmet needs (range 0‐47), 77% had ≥10 unmet needs, and 48% of the 47 needs were unmet on average. Strong positive correlations were found between K10 distress and the number of sibling/offspring unmet needs ( r  = 0.599 and r  = 0.522, respectively, P  = .00). Conclusions: Australian AYA siblings and offspring impacted by familial cancer experience high levels and numbers of unmet needs and substantial distress. Strong associations were found between increased distress and more unmet needs. Distress levels were comparable to AYAs seeking treatment for mental health issues. Insights into the type and number of needs experienced by AYA siblings and offspring will facilitate development and delivery of targeted, age‐appropriate interventions, and resources for these vulnerable and underserved young people.